Sex differences in the rapid and the sustained antidepressant-like effects of ketamine in stress-naïve and "depressed" mice exposed to chronic mild stress. (2nd April 2015) - Franceschelli, A.; Sens, J.; Herchick, S.; Thelen, C.; Pitychoutis, P.M.
Highlights: Female C57BL/6J mice are more sensitive to the rapid and sustained antidepressant effects of ketamine in the FST. Ketamine affected the levels of excitatory amino acids in a brain region-selective and sex-dependent manner. Ketamine treatment induced sex-differentiated behavioral effects in mice subjected to the CMS model of depression. Abstract: During the past decade, one of the most striking discoveries in the treatment of major depression was the clinical finding that a single infusion of a sub-anesthetic dose of the N-methyl-d -aspartate receptor antagonist ketamine produces a rapid (i.e. within a few hours) and long-lasting (i.e. up to two weeks) antidepressant effect in both treatment-resistant depressed patients and in animal models of depression. Notably, converging clinical and preclinical evidence support that responsiveness to antidepressant drugs is sex-differentiated. Strikingly, research regarding the antidepressant-like effects of ketamine has focused almost exclusively on the male sex. Herein we report that female C57BL/6J stress-naïve mice are more sensitive to the rapid and the sustained antidepressant-like effects of ketamine in the forced swim test (FST). In particular, female mice responded to lower doses of ketamine (i.e. 3 mg/kg at 30 min and 5 mg/kg at 24 h post-injection), doses that were not effective in their male counterparts. Moreover, tissue levels of the excitatory amino acids glutamate and aspartate, as well as serotonergic activity, were affected in a sex-dependent manner in the prefrontal cortex and the hippocampus, at the same time-points. Most importantly, a single injection of ketamine (10 mg/kg) induced sex-dependent behavioral effects in mice subjected to the chronic mild stress (CMS) model of depression. Intriguingly, female mice were more reactive to the earlier effects of ketamine, as assessed in the open field and the FST (at 30 min and 24 h post-treatment, respectively) but the antidepressant potential of the drug proved to be longer lasting in males, as assessed in the splash test and the FST (days 5 and 7 post-treatment, respectively). Taken together, present data revealed that ketamine treatment induces sex-dependent rapid and sustained neurochemical and behavioral antidepressant-like effects in stress-naïve and CMS-exposed C57BL/6J mice.